2014
DOI: 10.1007/s00412-014-0502-9
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic modifications in sex heterochromatin of vole rodents

Abstract: The genome of some vole rodents contains large blocks of heterochromatin coupled to the sex chromosomes. While the DNA content of these heterochromatic blocks has been extensively analyzed, little is known about the epigenetic modifications controlling their structure and dynamics. To better understand its organization and functions within the nucleus, we have compared the distribution pattern of several epigenetic marks in cells from two species, Microtus agrestis and Microtus cabrerae. We first could show th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 76 publications
2
3
0
Order By: Relevance
“…Furthermore, we also investigated several euchromatic marks such as H3K4 dimethylation (H3K4me2), H4K8 acetylation (H4K8ac), H3K9 acetylation (H3K9ac), as well as the level of DNA methylation (Additional file 1A). As shown before for male vole cells [23], the heterochromatic blocks from the X chromosomes of female Microtus cabrerae cells were depleted of euchromatic marks and their DNA was hypomethylated. In a previous study in male cells from voles, these repeats were shown to be transcribed [23].…”
Section: Resultssupporting
confidence: 53%
See 3 more Smart Citations
“…Furthermore, we also investigated several euchromatic marks such as H3K4 dimethylation (H3K4me2), H4K8 acetylation (H4K8ac), H3K9 acetylation (H3K9ac), as well as the level of DNA methylation (Additional file 1A). As shown before for male vole cells [23], the heterochromatic blocks from the X chromosomes of female Microtus cabrerae cells were depleted of euchromatic marks and their DNA was hypomethylated. In a previous study in male cells from voles, these repeats were shown to be transcribed [23].…”
Section: Resultssupporting
confidence: 53%
“…As shown before for male vole cells [23], the heterochromatic blocks from the X chromosomes of female Microtus cabrerae cells were depleted of euchromatic marks and their DNA was hypomethylated. In a previous study in male cells from voles, these repeats were shown to be transcribed [23]. Hence, we performed transcription run-on analysis and measured the relative amount of nucleotide incorporation within the differently marked heterochromatic blocks.…”
Section: Resultssupporting
confidence: 53%
See 2 more Smart Citations
“…The Y chromosome is morphologically similar between the two species, but the one in karyotype K is almost entirely heterochromatic, whereas that in karyotype L does not have evident CH (Fig 4C). This difference may reflect CH addition/deletion events or epigenetic mechanisms leading to the formation of heterochromatin [23][24][25]. The difference between the diploid numbers can be attributed to fusion-and/or fission-based chromosomal rearrangements, pericentric inversions and/or centromeric transpositions [26].…”
Section: Discussionmentioning
confidence: 99%